2011
DOI: 10.1007/s00134-011-2323-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal duration of a sustained inflation recruitment maneuver in ARDS patients

Abstract: In early-onset ARDS patients, most of the recruitment occurs during the first 10 s of a sustained inflation RM. However, hemodynamic impairment is significant after the tenth second of RM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 33 publications
0
37
0
5
Order By: Relevance
“…The optimal duration of a sustained inflation recruitment maneuver in subjects with ARDS was evaluated by Arnal et al, 23 who applied a 40-cm H 2 O sustained inflation for 30 s in 50 subjects within the first 24 h of meeting ARDS criteria. They found that most of the recruitment occurs during the first 10 s of the maneuver, but hemodynamic impairment was significant after 10 s of initiation.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
“…The optimal duration of a sustained inflation recruitment maneuver in subjects with ARDS was evaluated by Arnal et al, 23 who applied a 40-cm H 2 O sustained inflation for 30 s in 50 subjects within the first 24 h of meeting ARDS criteria. They found that most of the recruitment occurs during the first 10 s of the maneuver, but hemodynamic impairment was significant after 10 s of initiation.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
“…The first to be introduced-and until quite recently the most widely employed-was the application of 35-40 cmH 2 O airway pressure for 30-40 s. On rare occasion, even higher pressures may be needed to pry open large numbers of the most stubborn lung units, with some authors describing success with pressures that considerably exceed 50 cmH 2 O [6,7]. Because optimal duration of high pressure application varies inversely with pressure amplitude, the effective time of application may not be nearly as long as traditionally used at the bedside, as the data of this study indicate [3].…”
mentioning
confidence: 73%
“…The findings reported by Arnal et al [3] are hardly surprising, given the results of laboratory intercomparisons of recruiting maneuver techniques [11]. In these studies, sustaining high pressure was no more effective than using pressure-controlled ventilation (PCV) that achieved the same plateau value but was associated with more profound hypotension.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The most commonly used recruitment method is application of a constant airway pressure of 35-40 cm H 2 O for 30 -40 s. This recruitment maneuver improves oxygenation, but also has been associated with self-limited and of short duration hemodynamic compromise. 77 A recent report suggests that most of the recruitment occurs within the initial 10 s of the maneuver and that hemodynamic compromise is likely to occur after 10 -15 s. 78 Arnal et al studied 50 patients with early ARDS. A 40 cm H 2 O recruitment maneuver was applied for 30 s. They found that 50% of the recruited volume was attained within 1.6 s, 95% within 6.8 s, and Ͼ 98% with 10 s of applying the pressure.…”
Section: Acute Lung Injury and Acute Respiratory Distress Syndromementioning
confidence: 99%